2015
DOI: 10.1111/jeb.12711
|View full text |Cite
|
Sign up to set email alerts
|

Selection on incremental variation of eye size in a wild population ofDaphnia

Abstract: Several studies of eye morphology have analysed macroevolutionary patterns in the diversity of eyes, and although these studies are often linked to environment or behaviour, they provide only indirect evidence of selection. Specific data to show the microevolutionary potential for adaptation by natural selection in eye morphology have been lacking. We document directional selection on eye size, an important determinant of visual capabilities, in a wild population of the freshwater microcrustacean Daphnia. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…() showed that eye size is under selection in a natural population of Daphnia and also that changes in eye size have clear fitness consequences; small increases (∼1%) in the eye diameter of Daphnia obtusa increase reproductive outputs by 20% (Brandon et al. ). Research on bluefin killifish explored plasticity in opsin expression in fish under different light conditions (Fuller et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…() showed that eye size is under selection in a natural population of Daphnia and also that changes in eye size have clear fitness consequences; small increases (∼1%) in the eye diameter of Daphnia obtusa increase reproductive outputs by 20% (Brandon et al. ). Research on bluefin killifish explored plasticity in opsin expression in fish under different light conditions (Fuller et al.…”
Section: Discussionmentioning
confidence: 99%
“…This variation provides the raw materials for contrasting ecological conditions to favor evolutionary shifts in eye size and structure, but tests for microevolutionary shifts in eye size are conspicuously absent (but see Brandon et al. ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, studies have shown that ecological factors such as habitat complexity, foraging, diel activity and predation are associated with evolved differences in eye size (Banks, Sprague, Schmoll, Parnell, & Love, ; Beston, Dudycha, Post, & Walsh, in press; Beston, Wostl, & Walsh, ; Brandon, James, & Dudycha, ; Caves et al, ; Glazier & Deptola, ; Hammerschlag et al, ; Thomas et al, , ; Veilleux & Kirk, ; Zaret & Kerfoot, ). Although such studies provide information on the relationship between eye size and the environment, the vast majority of this work has compared eye size across species (but see Beston, Wostl, et al, ; Beston et al, in press; Brandon et al, ; Lönnstedt, McCormick, & Chivers, ). Despite years of research, very little work has experimentally tested how natural selection shapes the evolution of complex traits, such as the vertebrate eye.…”
Section: Introductionmentioning
confidence: 99%